Penerapan Sistem Informasi Manajemen sebagai Upaya Modernisasi Administrasi Pendidikan di Madrasah - Suharti, Tri; Mariam, Mariam (At Tadbir: Islamic Education Management Journal, 2025)
This study aims to analyze the implementation of Management Information System (SIM) as a strategy for modernizing educational administration at MTs Miftahul Ulum Cermenan Jombang. The main focus of this study is to analyze the extent to which the effectiveness of SIM implementation in improving the efficiency of administrative work, as well as identifying supporting and inhibiting factors in the implementation process. The research used a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, and documentation studies. Data were analyzed through the stages of reduction, presentation, and inductive inference. The results showed that the implementation of SIM has had a positive impact on accelerating access to academic data and work time efficiency, especially in managing student and teacher data. However, the implementation is not yet optimal because there is still dependence on manual systems, limited integration between work units, and the digitization of financial documents and correspondence. Supporting factors in the implementation of SIM include the commitment of madrasah leaders and the awareness of the importance of digitalization. Meanwhile, the main obstacles come from limited technological infrastructure, low digital literacy of administrative staff and unstable network quality. Thus, modernizing education administration through SIM requires a strategy to strengthen human resource capacity and improve infrastructure so that the system can run smoothly.